Iatrogenic Foreign Body in the Heart in Relation to Possible Malpractice and Its Consequences a Case Report - Karnecki, Karol; Kaliszan, Michał; Jankowski, Zbigniew (The Bulletin of Legal Medicine, 2015)
The paper presents the case of a 55-year-old man whose body was found at home at the foot of the stairs. The inspection of the body at the scene showed that the probable cause of the man’s death was positional asphyxia after falling down the stairs. The forensic autopsy revealed a 10-cm-long tip of a nephrostomy catheter. To determine the time and circumstances of the foreign body’s entry into the heart and its possible impact on the man’s death, the medical history was analyzed. It indicated that the piece of the catheter entered the circulatory system during surgery performed few years before man’s death. The results of the postmortem examination, taking into consideration the obtained medical information, excluded the foreign body in the right ventricle of the heart as a contributory cause of the man’s death.